An Update of Year 4 Results of the NSF S-STEM Scholarship Program at Shepherd University - Wang, Qing; Monahan, Robert; DEWITT, AMY; WILLIAMS-MCNAMEE, HANNAH; LIAO, WEIDONG; Guzide, Osman (Proceedings of the West Virginia Academy of Science, 2025)
The Track II NSF S-STEM Program in the Computer Sciences, Mathematics, and Engineering Department at Shepherd University started in October 2021 and has thus far supported 36 scholars majoring in computer science, mathematics, data analytics, or engineering. The overall goal of the program is to increase the number and quality of STEM graduates in the STEM workforce by providing financial, academic, and social support, which enables qualified students to overcome certain barriers that prevent them from meeting their educational and career goals. In this poster, the most significant activities and outcomes of the program since its inception are presented. Survey results and outcomes from the last academic year, along with initiatives that increase, retain, and support students in CME fields, are also discussed. This program has been supported by the NSF S-STEM Grant (award No. DUE-2130267).